PHARMACY OF THE FUTURE: DEVELOPMENT OF THE THEMATIC IMPROVEMENT CYCLE "LATEST DISCOVERIES AND PROSPECTS IN THE FIELD OF PHARMACY" - Shapovalova, Вікторія; Osyntseva, Аліна; Malekh, Надія; Shapovalov, Валерій (Actual Problems of Medicine and Pharmacy, 2024)
The mass introduction of artificial intelligence into pharmaceutical science and medical technologies in the system of legal relations "doctor-patient-pharmacist" causes significant changes in the light of modern scientific discoveries and technological innovations. In order to ensure this, the successful implementation of the training program conducted by the Department of Pharmacy of the Faculty of Postgraduate Education of the Higher Private Educational Institution "Lviv Medical University" of the cycle of thematic improvement "Latest discoveries and prospects in the field of pharmacy" is required. This is an important step in the direction of continuous professional growth of specialists in the field of pharmacy. The relevance of the thematic improvement cycle is recognized as an important factor in supporting professional development in the pharmaceutical industry. Listeners of this cycle get the opportunity to familiarize themselves with the latest achievements and trends in pharmacy, which contributes to deepening their knowledge and understanding of modern challenges. The cycle contributes to the development of key competencies of specialists in the field of pharmacy, which is important for their successful professional activity. The use of innovative teaching methods, such as the Moodle platform, further emphasizes the importance of modernizing the educational process in accordance with modern requirements. At the same time, the cycle of thematic improvement stimulates the development of the sphere of health care and pharmacy. Contributes to increasing the level of professional competence of participants in the "doctor-patient-pharmacist" legal relationship. Improves the quality, timeliness and availability of personalized medical and pharmaceutical care. All these factors emphasize the importance and effectiveness of the cycle of thematic improvement, as well as its significant place in the modern system of postgraduate professional training and development of pharmacy.